Therapeutic Prospects of Polysaccharides for Ovarian Cancer - Wang, Kaili; Cai, Mengcheng; Sun, Shuai; Cheng, Wen; Zhai, Dongxia; Ni, Zhexin; Yu, Chaoqin (Frontiers in Nutrition, 2022)
Ovarian cancer (OC) is ranked the first cause of death among the cancers of the female reproductive tract. The first-line platinum treatment is facing the sever challenge of patient relapse and poor prognosis. Thus, it is very imperative to develop natural antitumor drugs for OC with high efficiency. Natural polysaccharides have significant biological activities and greatly antitumor effects. Our analyzed and summarized work has further demonstrated of polysaccharides play key roles via inhibiting cell proliferations and growth, regulating tumor cell cycle, inducing cell apoptosis, suppressing tumor cell migration and invasion, improving the immunity-modulatory activities, and enhancing the efficacy of chemo-therapy (cisplatin) in OC, which have further provided the powerful supports and evidence for this viewpoint that polysaccharides have great application prospects of being developed as novel anticancer agents and supplementary remedy with an adjunct therapeutical agent or a manner of combining cisplatin for preventing and treating OC.